5-HT1A Receptors Alter Temporal Responses to Broadband Vocalizations in the Mouse Inferior Colliculus Through Response Suppression - Gentile Polese, Arianna; Nigam, Sunny; Hurley, Laura M. (Frontiers in Neural Circuits, 2021)
Neuromodulatory systems may provide information on social context to auditory brain regions, but relatively few studies have assessed the effects of neuromodulation on auditory responses to acoustic social signals. To address this issue, we measured the influence of the serotonergic system on the responses of neurons in a mouse auditory midbrain nucleus, the inferior colliculus (IC), to vocal signals. Broadband vocalizations (BBVs) are human-audible signals produced by mice in distress as well as by female mice in opposite-sex interactions. The production of BBVs is context-dependent in that they are produced both at early stages of interactions as females physically reject males and at later stages as males mount females. Serotonin in the IC of males corresponds to these events, and is elevated more in males that experience less female rejection. We measured the responses of single IC neurons to five recorded examples of BBVs in anesthetized mice. We then locally activated the 5-HT1A receptor through iontophoretic application of 8-OH-DPAT. IC neurons showed little selectivity for different BBVs, but spike trains were characterized by local regions of high spike probability, which we called ‘response features’. Response features varied across neurons and also across calls for individual neurons, ranging from 1-7 response features for responses of single neurons to single calls. 8-OH-DPAT suppressed spikes and also reduced the numbers of response features. The weakest response features were the most likely to disappear, suggestive of an ‘iceberg’-like effect in which activation of the 5-HT1A receptor suppressed weakly suprathreshold response features below the spiking threshold. Because serotonin in the IC is more likely to be elevated for mounting-associated BBVs than for rejection-associated BBVs, these effects of the 5-HT1A receptor could contribute to the differential auditory processing of BBVs in different behavioral subcontexts.